Effect of Organizational Commitment, Work Environment and Work Stress on Job Satisfaction of Radiology Installation Employees at Hospital: Pengaruh Komitmen Organisasi, Lingkungan Kerja dan Stres Kerja Terhadap Kepuasan Kerja Karyawan Instalasi Radiologi Rumah Sakit - Utami, Linda Muji; Prapanca, Detak (Indonesian Journal of Law and Economics Review, 2023)
The purpose of this study was to determine the effect of organizational commitment, work environment and work stress on job satisfaction of radiology installation employees at RSUD Sidoarjo.This study uses a type of quantitative research. The technique used in this study is a non-probability sampling technique with a saturated sample, which is a sampling technique if all members of the population are used as research samples. The sample size in this study were 77 employees of the radiology installation at RSUD Sidoarjo.The results of the study found that organizational commitment partially and simultaneously positive effect on job satisfaction, work environment partially and simultaneously positive effect on job satisfaction and job stress negatively affects job satisfaction.